Maskulinitas Beracun pada Laki-Laki Pelaku Cosplay Anime Jepang - Noor, Muhammad Aidin; Damaiyanti , Varinia Pura (Prodi Sosiologi FISIP ULM, 2024)
The emergence of men as cosplayers changes society's view of the role of men who are considered to always be dominant. The purpose of this study is to find out and describe the behaviour represented by men, especially for Japanese anime cosplayers and to find out how society treats the behaviour shown. This research uses a qualitative method with a phenomenological approach. While data collection techniques through observation, interviews, and documentation. The data analysis technique uses data reduction steps, data presentation and conclusion drawing. This research uses Lamert's labelling theory and Derrida's social deconstruction. The results showed that there is labelling given by society to cosplayers. In addition, there is a change in meaning in the social view that has been formed, which has turned into a new understanding. Male cosplayers acknowledge that crossdressing is a way for them to channel their hobbies and express themselves in the midst of a society that always demands men to have a masculine spirit. However, society still cannot fully accept the existence of men who behave and look like women, because they see restrictions on the values and norms that apply in society. Labelling includes wibu smelly onions and introverts, men who cosplay strangely, sissies and bencong, perverts to fanservice and are part of the LGBT who are considered sexual criminals. The social deconstruction obtained is that not all masculine is always associated with body shape and behaviour, but rather the purpose and how they behave in the surrounding environment.